Challenges of Digital Adoption for Women in India’s Tourism Gig Economy - Dwivedi, Santosh Kr.; Bharti, Mandeep; Sharma, Pankaj (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The tourism industry in India is becoming a platform for female entrepreneurship in the gig economy. It introduces a vast horizon of possibilities to women whose ventures are flexible and platform-based, including curating cultural experiences, becoming a freelance tour guide, and offering home stays. A key challenge is the aspect of digitalisation, particularly among women in rural and tier-2 or tier-3 cities. This paper examines the barriers to digital adoption, including low levels of digital literacy, limited access to technology, and socio-cultural inhibitions. This paper examines the impact of entrepreneurship on gender and socioeconomic status, as well as its relationship with policy, drawing on feminist technology studies and the digital divide model. Using data generated by quantitative analysis and qualitative case studies in Rajasthan, Kerala, and Northeast India, the paper identifies the key barriers and their associated economic implications. As it aligns with Sustainable Development Goals (SDGs) 5 (Gender Equality) and 8 (Decent Work and Economic Growth), the findings necessitate the prioritisation of interventions to overcome skilled labour shortages and include the gender-sensitive design of platforms and gender-specific digital training as a way to attract more women.